Self-Esteem Moderates the Effect of Compromising Thinking on Forgiveness Among Chinese Early Adolescents - Hong, Wei; Liu, Ru-De; Ding, Yi; Oei, Tian Po; Fu, Xinchen; Jiang, Ronghuan; Jiang, Shuyang (Frontiers in Psychology, 2020)
Forgiveness contributes to positive social relationship, which is critical for individual development, particular for early adolescents. Most previous studies focused on the unique roles of cognitive factors (e.g., compromising thinking) and personality traits (e.g., self-esteem) in the process of developing forgiveness. However, sporadic research has examined their interactive effect from an integrated perspective. Given that forgiveness has been categorized into decisional and emotional forgiveness, this study aimed to examine the effects of compromising thinking on two types of forgiveness, and the moderating effects of self-esteem on the association between compromising thinking and forgiveness among early adolescents. A total of 1,009 Chinese primary and secondary school students (50.4% males; M age = 11.75, SD = 1.27) were recruited to complete three self-reported questionnaires. The results showed that compromising thinking predicted decisional forgiveness but not emotional forgiveness. Furthermore, self-esteem was identified to moderate the conditional effects of compromising thinking on decisional and emotional forgiveness. These findings advance a better understanding of the construct and mechanism of forgiveness, which can provide insights for targeted forgiveness interventions among early adolescents, such as compromising thinking instructions and self-esteem enhancement programs.